Stylistic marking notion of language means and devices (general theoretical aspect) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
This article investigates the basic linguistic approaches of defying stylistic marking of language means and devices. Stylistic marking (stylistic expressiveness) is considered as supplying a language unit  with additional connotative information expressing emotional, evaluative or stylistic nature. It determines the ability of the unit to create a stylistic effect. It also forms special effect to the speaker’s message according to communicative and pragmatic speaker’s intentions, making the speech more ceremonial and high spirited, informal, familiar, ironic, humorous, comic, rude, aggressive etc. The concept, known in linguistics called stylistic marking, covers a wide range of material and functionally disparate phenomena. Stylistically be labeled individual sounds or their compound word word creative means, syntactic constructions and so on. The article discusses some of the interpretations of the deadline and it being denoted linguistic phenomena.It is noted that in modern linguistics phenomenon stylistic marking understood differently. Some researchers consider it in relation to the concept of linguistic rules, other scientists notion of stylistic markedness associated with stylistic value and the presence of a linguistic unit different connotations. At the same time in the style widely used term “stylistic expressiveness”, which usually means a linguistic unit correlation with certain functional style language. Some researchers stylistic expressiveness is defined as the presence of additional words semantic and stylistic nuances.
Keywords: stylistic marking; stylistic expressiveness; language norm; stylistic meaning; connotation